PTH-108 The hidden burden of faecal incontinence in active and quiescent ulcerative colitis: an underestimated problem?. (June 2019) - Nigam, Gaurav B; Limdi, Jimmy K; Hamdy, Shaheen; Vasant, Dipesh H
Abstract : Introduction: Despite advances in Ulcerative Colitis (UC) therapies, many patients suffer refractory defaecatory symptoms in the absence of active inflammation. For this group, treatment remains challenging, with a paucity of research and limited therapeutic options. In this prospective, ongoing study, we aim to determine the prevalence of faecal incontinence (FI) in patients with quiescent UC. Methods: In a cross-sectional study, consecutive patients with UC attending Inflammatory Bowel Disease (IBD) clinics were invited to participate. Patients completed a series of validated questionnaires; including an IBD-specific FI questionnaire (ICIQ-IBD questionnaire), Hospital Anxiety and Depression Scale (HADS), the Rome IV diagnostic questionnaire, and the IBD-control questionnaire. Participants were requested to return a Faecal Calprotectin (FCP) within 2 weeks of completing questionnaires. Quiescent UC was defined as IBD-control 8 score ≥13 and IBD-control-VAS ≥85, and/or FCP levels ≤250 (where available, FCP data were used in preference to IBD-control to classify UC activity). Data were compared between active and quiescent groups using chi-square and non-parametric tests. Results: Overall, n=97 UC patients (n=50 males, mean age 48 (range 18–82) participated. ICIQ-IBD data revealed that most patients experience FI (84/97 (87%) during 'relapses'. Interestingly, 58/97 (60%) reported FI when in 'remission', and this group had higher median HADS depression (P=0.0002), poorer QoL scores (P<0.0001), and trend towards higher HADS anxiety (P=0.09) scores, compared to those without FI. Disease activity data (IBD-control and/or FCP) were available for all patients, and based on these 61/97 (63%) had quiescent UC. The prevalence of FI based on ICIQ-IBD did not differ between those with active (22/36, 61%) and quiescent UC (36/61, 59%), P=NS. In those with FI on ICIQ-IBD, median IBD-FI symptom scores, IBD-FI QoL scores and HADS (anxiety: P=0.47, depression: P=0.18) did not differ between disease activity groups. However, within the quiescent group, patients that met the more stringent Rome IV criteria for FI (n=13) had higher median IBD-FI symptom scores (P=0.007) and HADS-depression scores (P=0.05), a trend to worse IBD-FI QoL (P=0.07), but similar HADS-anxiety (P=0.68). Conclusion: This study is one of the first to identify that regardless of disease activity, FI affects most patients with UC, detrimentally impacting patients' psychological wellbeing, impairing their QoL, and should therefore routinely be screened for in clinics. There is an urgent need for further research in the often neglected area of FI and quiescent disease.